Oribatid mites (Acari: Oribatida) from roofs of houses in Sogn og Fjordane (Norway) - Graczyk, Radomir; Seniczak, Stanisław (Biological Letters, 2014)
Oribatid mite communities in moss covering the roofs of buildings in towns of Bolstad, Luster, and Sørheim (in Sogn og F jordane, Norway) were investigated. These mites were rather numerous and rich in species, which was caused mainly by the natural roofing material (rock slates) and the temperate and rather stable maritime climate. In these communities the most abundant were Tectocepheus velatus, Dissorhina ornata, Oppiella uliginosa, Quadroppia quadricarinata, and Oribatula exilis, which are typical soil species. Adults usually dominated in the mite communities, except for Bolstad, where the juveniles were slightly more abundant than the adults. Phauloppia lucorum and Trhypochthonius tectorum were the only species of the group of typical inhabitants of roofs of buildings, but were not numerous in Sogn og Fjordane. In continental climate these species are often abundant on roofs of buildings.